2013
DOI: 10.1074/mcp.m113.027953
|View full text |Cite
|
Sign up to set email alerts
|

The GlycoFilter: A Simple and Comprehensive Sample Preparation Platform for Proteomics, N-Glycomics and Glycosylation Site Assignment

Abstract: Current strategies to study N-glycoproteins in complex samples are often discrete, focusing on either N-glycans or N-glycosites enriched by sugar-based techniques. In this study we report a simple and rapid sample preparation platform, the GlycoFilter, which allows a comprehensive characterization of N-glycans, N-glycosites, and proteins in a single workflow. Both PNGase F catalyzed de-N-glycosylation and trypsin digestions are accelerated by microwave irradiation and performed sequentially in a single spin fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…As a demonstration of the method, the partially occupied glycosylation site of bovine fetuin at Asn-158 was studied [16-17]. As a first step, we verified that no additional PTMs were present on this peptide.…”
Section: Resultsmentioning
confidence: 74%
“…As a demonstration of the method, the partially occupied glycosylation site of bovine fetuin at Asn-158 was studied [16-17]. As a first step, we verified that no additional PTMs were present on this peptide.…”
Section: Resultsmentioning
confidence: 74%
“…If a specific motif was identified in the deglycosylated form and also identified in either of the other two forms, this indicated that that motif was partially glycosylated [8]. When all motifs were compared, evident differences were observed among the results from three search engines (Figure 1a -c).…”
Section: N-glycosylation Consensus Motifs Analysismentioning
confidence: 98%
“…The depletion of albumin in urine was performed according to a published one-step protocol [15], and the protein concentration was measured by the Bradford assay in triplicate. Approximately 250 µg of depleted urinary proteins from each donor were further processed according to the GlycoFilter platform to obtain released N-glycans and tryptic peptides [8], respectively. PNGase F catalyzed de-N-glycosylation was carried out in a H 2 18 O buffer via a 20-min domestic microwave protocol [16].…”
Section: Urine Processingmentioning
confidence: 99%
See 2 more Smart Citations